The Kyiv meridian axial circle with a CCD micrometer - Karbovsky, V. (Кинематика и физика небесных тел, 2005)
The Kyiv meridian axial circle (MAC) is a refractor (D = 0.18 m, F = 2.3 m) which is used now in a CCD astrometric survey of the equatorial zone. In 2001, it was equipped with a ISD017AP CCD having 1040×1160 pixel, 16 mkm pixel size, and 1.394" per pixel scale. The dark current is 7e⁻/pixel/s, the readout noise is 18e−, the output amplifier responsiveness is 3.3 μV/e⁻. The photometric system of the MAC reproduces standard V photometric system; the limiting magnitude is about V =17. Star pixel coordinates are measured with an accuracy of 0.02 pixel and star fluxes to 0.02 mag. The frame size is 24'×28'. Observations are obtained in the drift-scan mode allowing to form images of moving objects at telescopes without the moving parts. Exposure time is 108 sec δ s while the scan length may reach hours. Observed data are stored on CD disks. It was estimated that image degradation for this CCD micrometer owing to CCD distortion amounts to 4.9"tan δ in right ascension and 1.2"tan δ in declinations, therefore, the declination zone of observations was limited to 30 degrees. A special software is used for reduction of observations.